(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective Objective of this study is to compare the diagnostic accuracy of cancer antigen 125 and ultrasonography in differentiation between benign and malignant ovarian masses by taking histopathology as gold standard.. Study Design Comparative cross-sectional study Sample Size One hundred patients who were proven histologically to have ovarian masses were taken. Setting Department of Gynaecology & Obtetrics Unit-1, Sir .Ganga Ram Hospital, Lahore Duration with Dates One year from 03-03-2008 to 02-03-2009. Sampling Technique Convenient non-probability sampling Inclusion Criteria Above the age of fifteen years with histopathologically proven ovarian masses • Suitable for surgery. Exclusion Criteria • Pregnancy with ovarian mass. • Hydatid cyst of ovary. Data Collection One hundred patients with ovarian masses were selected for this study. Blood samples were collected preoperatively for measurement of serum CA125 from these patients. Various cutoff levels of CA125 were used to classify masses into benign or malignant ones. All these patients also had preoperative ultrasound examination. Ultrasound echo pattern recognition was used to a mass as benign or malignant. Results from both assays were then compared with histological findings after surgery. Statistical Analysis The collected data was transferred into SPSS version 12 and analysed through this statistical programme. Descriptive statistics had been calculated. Age, duration of menstrual cycle, age of menarche and menopause (where applicable) and level of cancer antigen 125 had been calculated as mean and standard deviation. While education, marital status, occupation had been presented as percentages. Sensitivity, Specificity, Positive predictive value, Negative predictive value had been calculated by using histopathology as gold standard. Specific variable (type of tumour) had been associated with demographic variable, association that had been tested for significance by applying Chi Square test as this variable was qualitative in nature. P value equal to or less than 0.05 was considered significant. Results One hundred patients of ovarian masses were selected. Benign masses were 78% and 22% were malignant. The most common clinical presentation was abdominal pain followed by abdominal mass. The sensitivity and specificity of CA125, at cutoff level of 35U/ml were 82% and 83% respectively to classify masses into benign or malignant ones. Ultrasonographic differentiation of benign and malignant ovarian tumours showed results with a sensitivity of 86% and specificity of 87%. Conclusion It is concluded that there is a 22% risk of malignancy in patients presenting with an ovarian mass. Women especially in the reproductive age presenting with abdominal pain should be carefully evaluated for a ovarian mass. Anechoic masses have high probability of being benign and possibility of malignancy increases with the presence of solid component. CA125 has lower sensitivity and specificity than that of ultrasonography for discrimination between benign and malignant ovarian masses.